Molecular epidemiology of Paenibacillus larvae larvae and incidence of American foulbrood in Argentinean honeys from Buenos Aires province - Alippi, Adriana Mónica (2004)
Paenibacillus larvae larvae, the causative agent of American foulbrood disease of honey bee larvae occurs throughout the world and is found in all beekeeping areas of Argentina. Microbiological analysis of 394 honey samples obtained from bee hives from Buenos Aires province (Argentina) from three years of sampling (1999–2001) yielded 219 positive cases (55.6%). The incidence of P. l. larvae infected honey samples for 1999 was 68.1% (n = 160), for 2000 47.1% (n = 102), and 46.2% for 2001 (n = 132). The mean values of spore contamination for the three-year study showed a continuous reduction, probably due to good practices of disease management by beekeepers by breeding bees for hygienic behaviour and reduction of antibiotic treatments for control of AFB. P. l. larvae populations isolated from honey were characterized on the basis of DNA fingerprints using the repetitive-sequence-based polymerase chain reaction technique (rep-PCR) with BOX- and REP- sequencespecific primers. Four distinctive patterns, named A, B, C, and D, were distinguishable among the isolates. Genotype D was not observed in previous studies; this finding could be correlated with a new introduction of the disease in Argentina since 1997 when only three genotypes (A, B, and C) were confirmed. The rep-PCR fingerprint patterns obtained were compared with the patterns generated by a world-wide collection of P. l. larvae strains. The same 4 genotypes patterns were found within a collection of strains from 18 different countries of the world. It is important to point out that pattern C was only found in Argentina and in one sample from Uruguay located in the border line, suggesting that genotype C could have been derived from genotype A and disseminated to Uruguay from Argentina. These findings support the hypothesis that American foulbrood disease is exposed to a limited selective pressure from climatic and environmental sources.